Critical Dscourse Analysis on The Issue of Environmentally and Socially Damaged Nickel Mining for the Benefit of Foreign Countries in The Media of Fajar Malut - Hi Saleh, Zulkifli; Ajwan, Alkadri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
The problem discussed in this study is a negative politeness strategy. The method used in this study is a qualitative descriptive method because it aims to describe and classify various negative politeness strategies in the KompasTV YouTube video about the talk show "Why Batak People Become Lawyers" in the series "The Interview with Tukul Eps 2 Part 5 ". The results of this study are the first. The negative politeness strategy "minimise the imposition (reduce the power or threat to the face of the interlocutor)" namely "please please from Bang Ruhut first, please", second. A negative politeness strategy by showing a pessimistic attitude is to make sure, third. The negative politeness strategy "question, hedge (using the form of a question with a certain particle)" namely the word 'continue', fourth. The negative politeness strategy "give deference (pay respect)" is at the beginning of the sentence using the word 'agree', where this sentence pays respect with approval to the speech partner/first guest star (Ruhut), fifth. The negative politeness strategy "go on record as incurring a debt, or as not indebting (states clearly that the speaker has given kindness/debt)" which is at the end of the sentence giving a gift.